Esketamine clinical trials: reply to Maju et al. - Gastaldon, C. (Epidemiol Psychiatr Sci, 2020)
Maju et al. provided clarifications on important and controversial issues related to esketamine clinical trial data, in response to a vivid debate triggered by the marketing authorisation recently granted by this new medicine. In this commentary, we reply to their comments attempting to critically discuss the evidence base needed to obtain regulatory approval.